Position-specific anthropometry and throwing velocity of elite female water polo players - Martinez, J. G.; Vila, M. H.; Ferragut, C.; Noguera, M. M.; Abraldes, J. A.; Rodriguez, N.; Freeston, J.; Alcaraz, P. E. (The Journal of Strength and Conditioning Research, 2015)
This study was conducted with the following aims: (a) to describe the effect of playing position on anthropometrics and throwing velocity in elite female water polo players and (b) to observe any relationships between anthropometric parameters and throwing velocity. To achieve these aims, we analyzed a total of 46 female elite players (age: 22.5 ± 5.1 years; height: 172.0 ± 6.9 cm, body mass: 67.4 ± 7.5 kg) members of the top 4 teams of the Spanish Honour Division women league (21 offensive wings players, 17 center, and 8 goalkeepers). Wings were significantly shorter and had smaller arm spans than goalkeepers and center players. Goalkeepers demonstrated longer forearm lengths than wing and center players. No other significant differences were evident between positions in terms of anthropometric, strength, or throwing velocity variables The somatotype of the offensive wing players was mesomorphic, whereas centers were endomorph (classified as endomesomorphic). Height, arm span, muscular mass, biepicondylar breadth of the humerus, arm girth (relaxed and tensed), and forearm girth were related to throwing velocity. In conclusion, only a small number of anthropometric differences exist between players of different positions in elite female water polo. Shorter players with smaller arm spans may be better suited to the wings, whereas athletes with longer forearms may be better suited to the goalkeeper position. Taller, more muscular athletes with wider arm spans, broader humeri, and wider arms (relaxed and flexed) tended to throw with increased velocity. Trainers should focus on increasing the modifiable characteristics (muscle mass and arm girths) that contribute to throwing velocity in this population.